Beetroot Extract Improves Specific Performance and Oxygen Uptake in Taekwondo Athletes: A Double-Blind Crossover Study [Ekstrakt Z Buraka Ćwikłowego Poprawia Swoistą Wydolność I Pobór Tlenu U Zawodników Taekwondo: Badanie Typu Crossover Z Podwójnie Ślepą Próbą] - Aedo-Munoz, E (Idokan Poland Association, 2021)
Background. Nitrate-rich supplements such as beetroot extract could improve aerobic performance by increasing neuromuscular functioning. However, little is known about the effects of beetroot extract on combat sports, such as taekwondo. Problem and aim. This study investigated the acute effect of beetroot extract supplementation (1g) on taekwondo athletes undergoing a maximal aerobic test. Methods. Twelve athletes (26.8±8.8 yrs.; 77.8±11.7 kg; 1.8±0.1 m; 25.3±3.2 kg/m2; 10.0±5.3 Fat%) were submitted to a specific Taekwondo aerobic protocol. All participants performed an alternated kick (bandal-chagi) maximal protocol under two randomized conditions: a) beetroot extract; and b) Placebo. Results. Beetroot condition showed a higher absolute VO2Peak (4.0±0.6 vs. 3.6±0.5 L/min; p=0.048), absolute VO2max at anaerobic threshold (3.7±0.6 vs. 3.2±0.6 L/min; p=0.044), and complete stages (10.9±2.6 vs. 8.3±1.7 L/min; p=0.009). Lactate concentration increased significantly between measurements taken before, after and 3 min after (p<0.001) the test, without differences between conditions (p=0.46). Conclusion. Our results suggest an ergogenic effect of beetroot extract supplementation (1 g) on aerobic capacity and specific test performance in taekwondo athletes. © 2021 Idokan Poland Association. All Rights Reserved.